Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan dengan Pendekatan Customer Satisfaction Index (CSI) pada PT Astra International Tbk – TSO Auto2000 Cabang Salemba - Melisa Melisa; Purwatiningsih Purwatiningsih (STIKes Ibnu Sina Ajibarang, 2025)
The quality of service towards customer satisfaction in the automotive industry of Toyota car transportation in Indonesia is growing rapidly from year to year, especially in big cities in Indonesia this car is very much needed. The market conditions that are becoming wider and market opportunities are everywhere, this results in increasingly open and tight competition competing to be able to meet the needs and demands required by customers, customer satisfaction is a level where the estimated product performance is in accordance with the buyer's expectations and one of the ways of PT Astra International Tbk - TSO Auto2000 Salemba Branch to maintain the quality of service to customers. Customer Satisfaction Index (CSI) is a method for measuring customer satisfaction based on attributes to be measured such as compliance, responsiveness, assurance, and empathy. The purpose of the study is to improve the performance of service, facilities and customer handling of PT Astra International Tbk - TSO Auto2000 Salemba Branch. The overall level of customer satisfaction is in the good category with a CSI value of around 97%, indicating that customers are satisfied with the services provided by PT Astra International Tbk - TSO Auto2000 Salemba Branch. The factors that most influence customer satisfaction are the quality of staff service, including intimidation and speed of service.